2013
DOI: 10.3314/mmj.54.123
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Significance of Dermatophytes in Ismailia and Port Said Provinces, Egypt

Abstract: Background : Dermatophytes are common in both developed and developing countries, the species involved and the resulting clinical entities vary geographically. Aim of study: To determine public health importance of dermatophytes with special regard to the distribution of the zoophilic species among the examined human cases. Methods: Patient specimens(dermatophytosis-like lesions)were mycologically examined using direct microscopic and cultural examinations. Results: The overall dermatophyte infection rates amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similarly, 53% of the PV patients reported by Schlesinger et al (2002) displayed a positive fungal culture but exclusively grew Trichophyton rubrum in culture. The difference in the frequency of dermatophytes involved in the current study could be attributed to the fact that dermatophytes species vary geographically (Aboueisha and El-Mahallawy, 2013). …”
Section: Discussionmentioning
confidence: 92%
“…Similarly, 53% of the PV patients reported by Schlesinger et al (2002) displayed a positive fungal culture but exclusively grew Trichophyton rubrum in culture. The difference in the frequency of dermatophytes involved in the current study could be attributed to the fact that dermatophytes species vary geographically (Aboueisha and El-Mahallawy, 2013). …”
Section: Discussionmentioning
confidence: 92%
“…A single study contained definitive prevalence rate numbers relating both human and feline dermatophyte infections, with animal contact a risk factor in 56.7% of positive human cases, but did not differentiate cats from other animals (Boumhil et al 2010 ). Several studies commented on the rise of zoophilic species diagnosis in humans, and an increased representation in the isolates from skin lesions taken from dermatological patients (Benmezdad et al 2012 , Aboueisha and El-Mahallawy 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies showed that T. rubrum was the main species found among skin dermatophytosis in Tunisia, 61,89–91 and it was also predominant in other countries such as Algeria, Jordan, and Saudi Arabia 57,75,92 . However, several reports from Egypt and Libya reported T. violaceum as the main etiologic agent of Tinea corporis and other ringworm infections of the skin 8,47,58,93 . Additionally, zoonotic species including M. canis and T. mentagrophytes were frequent in Kuwait, Saudi Arabia, Palestine, and Egypt 66,69,74,94 .…”
Section: Species Distribution and Antifungal Resistance Among Dermato...mentioning
confidence: 99%